The effect of contamination disgust on Covid-19-related anxiety. (1st June 2022) - Santarelli, G.; Innocenti, M.; Faggi, V.; Galassi, F.; Castellini, G.; Ricca, V.
Abstract : Introduction: It is proven that high levels of disgust contribute to implementing protective behaviors. Investigators also discovered that the emotion of disgust plays a central role in determining anxiety related to the contraction of COVID-19. Few data are available about the role of the contamination disgust, a specific disgust domain, in this relationship. Objectives: The effect of contamination disgust on COVID-19-related anxiety was investigated. Methods: 295 healthy subjects were enrolled through an online survey. They completed Disgust Scale-Revised (DS-R) and were asked to estimate their levels of Covid-19-related anxiety in 12 proposed situations. A total score was then calculated. An ANOVA model having Covid-19-related anxiety total score as dependent variable, and DS-R contamination disgust, age, and sex as predictors was estimated. Results: The overall model was significant (F(3, 291)=6.402, p<0.001) and explained 6.2% of total Covid-19 anxiety variance (R 2 =0.062). The effect of DS-R contamination disgust on Covid-19-related anxiety was positive, significant (B=0.974, t(291)=3.227, p=0.001) and explained 3.5% of Covid-19-related anxiety variance (partial η 2 =0.035). A significant effect of sex was detected (F(1, 291)=4.919, p=0.027), with females having higher Covid-19-related anxiety than males, while no effect was detected for age (B=-0.024, t(291)=-0.884, p=0.377). Conclusions: The presented data provide preliminary evidence for an effect of contamination disgust on Covid-19-related anxiety. Disclosure: No significant relationships.